LEVERAGING COMMUNITY RADIO STATION (CRS) AS A TOOL TO EMPOWER RURAL COMMUNITY: A CASE STUDY OF ODISHA’S RADIO NAMASKAR - Akhter, Jawed (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A community radio station popularly abbreviated (CRS) is more than just an informational tool. The stories of many people are combined into the story of one community by its waves. Community media can delve deeper and document local events that mainstream media often ignores. By giving the community required access to information, updates, and assistance during emergencies, community radio stations are essential in helping to handle local crises. This study examines the role of community radio stations as a transformative instrument for strengthening rural communities with a case study of Odisha's Radio Namaskar. A thorough assessment of the radio station’s impact and its reach is expected to be achieved by methodically measuring factors. The study is expected to focus on social integration, economic empowerment, and cultural preservation as empowering factors of the community. The study will employ the quantitative method to assess the multidimensional impact of Radio Namaskar on people residing around the radio station. The research aims to improve the understanding of the role of a community radio that can help in supporting the rural development that the local community in Odisha has experienced. The findings of this study are expected to contribute to the discourse on the impact of community radio in fostering local empowerment and sustainable development. The study may provide insights on best practices that can help policymakers and community radio practitioners to leverage community radio stations as powerful tools for empowerment.